Optimasi Pendistribusian Makanan Ringan pada Algoritma Transportasi Menggunakan Metode Voge - Martini M. (Universitas Bina Sarana Informatika, 2017)
For some people or companies that produce product always want the maximum benefit with minimum expenditure. Food is the most widely-made product because it is plentiful consumed by the public. Many who take advantage of the food-making business to fulfil viability or just mere talent. We often encounter food produced by large companies, midsize companies, even their own business (home industry). Many of the constraints that are typically encounter on little business such as marketing difficulties, counting the number of the production and profits, price competition, or innovate and create various types of different taste. The expired of the pasty products surely are not long, therefore it needs good marketing by distributing an appropriate amount to the right place, given the competition for this type of food is very high. Few meters away could sell the same type of cake, so it is necessary to maintain the quality of taste and price. From the problem above the authors make a settlement with the transport algorithm using Vogel method that can simplify the distribution for cake makers to minimize the cost of production and determining the right amount on demand.Keywords: expired, Transport Algorithms, Methods Vogel, minimize production costs